Obsessive-compulsive disorder in the COVID-19 pandemic (Research, Society and Development, 2021)
The present study is bibliographical research with the objective of analyzing the changes suffered by Obsessive-compulsive Disorder (OCD) patients in the COVID-19 pandemic through the review of scientific articles available in the Pubmed database, chosen using the descriptors “Obsessive-compulsive disorder” and “COVID-19”, published from January 2020 to April 2021. The analysis based on the literature revealed the increase and change in the severity of the symptoms of OCD patients, especially in those who have contamination obsession and washing compulsion. The exacerbation of symptoms in patients was associated with a worsening of stress, anxiety and depression traits. Furthermore, it was observed the manifestation of obsessive-compulsive symptoms in the general population in that period. Therefore, future post-Covid-19 research is needed to assess how the clinical picture of patients with OCD exacerbation will evolve, as well as to determine whether new OCD symptoms in the general population are related to a definitive diagnosis of OCD, an expression of anxiety caused by the pandemic or a combination of both.